AKUNTABILITAS DAN TRANSPARANSI BANTUAN KEUANGAN PARTAI POLITIK DI KABUPATEN X - Permata Sari, Indah; Khairul (Media Mahardhika, 2024)
This research aims to analyze the accountability and transparency of financial assistance provided to political parties in a regency. The study employs observations and documentation to enhance data accuracy. Accountability is assessed using Koppell's four dimensions, while transparency is evaluated through Bovens' three perspectives. The findings reveal that accountability for political party financial assistance in the regency is weak, largely due to the lack of government oversight, which increases the risk of budget mismanagement or diversion. The roles of the Audit Board (BPK) and the Regional Government are limited to auditing, guiding, and monitoring, without any control over the financial assistance given to political parties. Furthermore, political parties have not fully complied with the requirements for submitting accountability reports. In terms of transparency, political parties receiving financial assistance have not effectively implemented transparent practices. There is a tendency for political parties to restrict access to financial information, limiting it to political circles, making it difficult for the public to obtain details about party performance. Additionally, the legal framework established by the government lacks sanctions for non-compliance with transparency requirements, which hinders the achievement of the intended level of public transparency.